Fermentation quality, aerobic stability, and microbiome structure and function of Caragana korshinskii silage inoculated with/without Lactobacillus rhamnosus or Lactobacillus buchneri - Wu, Baiyila; Ai, Juanjuan; Li, Tiyu; Qin, Weize; Hu, Zongfu; Siqin, Tuya; Wu, Tiemei; Wang, Chao; Niu, Huaxin (Frontiers in Sustainable Food Systems, 2023)
Caragana korshinskii is a forage shrub species with high-protein content that has been extensively used to alleviate feed shortages for ruminants in northern China. Herein, we investigated the effects of Lactobacillus rhamnosus and Lactobacillus buchneri on the fermentation quality, aerobic stability, and microbiome composition and the predicted functional characteristics of C. korshinskii silage. C. korshinskii silages were inoculated with and without L. rhamnosus or L. buchneri. After 14 and 56 days of ensiling, the aerobic stability was determined. The results revealed that after 14 and 56 days of ensiling, L. rhamnosus- and L. buchneri-inoculated silage exhibited increased acetic acid and lactic acid contents, whereas the pH and 2,3-butanediol and butyric acid contents were decreased compared with those of the control silage. The control silages that were opened at 14 and 56 d, deteriorated during the aerobic stability test, whereas silages inoculated with L. rhamnosus and L. buchneri did not exhibit any aerobic deterioration. The control silage showed an increased Clostridium and Bacillus abundance, whereas Lactobacillus abundance decreased compared with L. rhamnosus- and L. buchneri-inoculated silages, following the 7 days of aerobic exposure. The fermentation parameters were associated with microbial communities, including Lactobacillus, Pedicoccus, Weissella, Clostridium, and Bacillus. Carbohydrate and amino acid metabolisms in the control silage decreased after 7 days of aerobic exposure compared with lactic acid bacteria-inoculated silages. To conclude, next-generation sequencing combined with 16S ribosomal RNA gene-predicted functional analyses might provide new information about the silage quality during fermentation and the aerobic stability.